Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I'm looking for a reference for (or an elementary proof of) $$ \lim_{s \rightarrow 1} \left( \zeta(s) - \frac{1}{s-1} \right) = \gamma$$ Thanks for your help.

share|improve this question
    
Have you tried looking at the book by Sondow (home.earthlink.net/~jsondow) referenced by Wikipedia: en.wikipedia.org/wiki/…? –  JavaMan Jan 20 '12 at 16:25
    
The book "Gamma: Exploring Euler's Constant," by Julian Havilmay also have what you're looking for. –  JavaMan Jan 20 '12 at 16:30

3 Answers 3

up vote 16 down vote accepted

Elementary proof:

For $s>1$, write $$\zeta(s) - \frac{1}{s-1} = \sum_{n=1}^{\infty} \left( \frac{1}{n^s} - \int_{n}^{n+1} \frac{dx}{x^s} \right).$$ I will show below that we can interchange limits and summation. Assuming this, we have $$\lim_{s \to 1^{+}} \left( \zeta(s) - \frac{1}{s-1} \right) = \sum_{n=1}^{\infty} \left( \frac{1}{n} - \int_{n}^{n+1} \frac{dx}{x} \right).$$ (It is obvious that we can interchange limits with integration by just explicitly computing the integral.)

The sum of the first $N$ terms of the above is $$\sum_{n=1}^{N} \frac{1}{n} - \int_1^{N+1} \frac{dx}{x} = \sum_{n=1}^{N} \frac{1}{n} - \log(N+1).$$ So $$\lim_{s \to 1^{+}} \left( \zeta(s) - \frac{1}{s-1} \right) = \lim_{N \to \infty} \left( \sum_{n=1}^{N} \frac{1}{n} - \log(N+1) \right)$$ and the right hand side is, by definition $\gamma$.


We now justify interchanging limits. Set $$a_n(s) = \frac{1}{n^s} - \int_{n}^{n+1} \frac{dx}{x^s}=\int_n^{n+1} \left( \frac{1}{n^s} - \frac{1}{x^s} \right) dx.$$ We are going to use the Weierstrass $M$-test, which means that we must find a convergent series $\sum M_n$ such that, for all $s$, we have $|a_n(s)| < M_n$. Actually, it is enough to do for $s$ in the interval $[1,2]$, so I will assume this from now on. I'm sure there are many ways to come up with such a boundl this is the one I found first.

We have $$a_n(s) < \int_n^{n+1} \left( \frac{1}{n^s} - \frac{1}{(n+1)^s} \right) dx = \frac{1}{n^s} - \frac{1}{(n+1)^s}=\frac{1}{n^s} \left( 1- \frac{1}{(1+1/n)^s} \right)$$ $$ < \frac{1}{n} \left( 1- \frac{1}{(1+1/n)^2} \right) < \frac{1}{n} \cdot \frac{2}{n}.$$ At the line break, we used that $1/n^s$ is maximized at the left endpoint of $[1,2]$, and $1-1/(1+1/n)^s$ is maximized at the right endpoint.

So we take $M_n = 2/n^2$ and we are done.

share|improve this answer

Assume $s > 1$. Then $$\zeta(s) = \sum_{n=1}^\infty n^{-s} =\sum_{n=1}^\infty \left( \frac{1}{\Gamma(s)} \int_0^\infty t^{s-1} \mathrm{e}^{-n t} \mathrm{d} t \right) = \frac{1}{\Gamma(s)} \int_0^\infty t^{s-1} \frac{\mathrm{e}^{-t}}{1- \mathrm{e}^{-t}} \mathrm{d} t $$ Integrability at the lower bound of integration requires $s>1$. Since $\frac{1}{1-\mathrm{e}^{-t}} = t^{-1} + \frac{1}{2} + \mathcal{o}(t)$, we subtract the main term and split it off. We can do this for $s>1$ as both integrals converge: $$ \begin{eqnarray} \zeta(s) &=& \frac{1}{\Gamma(s)} \int_0^\infty t^{s-1} \mathrm{e}^{-t} \left( \frac{1}{1-\mathrm{e}^{-t}} - \frac{1}{t} \right) \mathrm{d} t + \frac{1}{\Gamma(s)} \int_0^\infty t^{s-2} \mathrm{e}^{-t} \mathrm{d} t \\ &=& \frac{1}{\Gamma(s)} \int_0^\infty t^{s-1} \mathrm{e}^{-t} \left( \frac{1}{1-\mathrm{e}^{-t}} - \frac{1}{t} \right) \mathrm{d} t + \frac{\Gamma(s-1)}{\Gamma(s)} \\ &=& \frac{1}{\Gamma(s)} \int_0^\infty t^{s-1} \mathrm{e}^{-t} \left( \frac{1}{1-\mathrm{e}^{-t}} - \frac{1}{t} \right) \mathrm{d} t + \frac{1}{s-1} \end{eqnarray} $$ The remaining integral is finite at $s=1$, and gives the free term in the expansion you seek. Accidentally, it also gives the integral representation for the Euler-Mascheroni constant: $$ \gamma = \int_0^\infty \mathrm{e}^{-t} \left( \frac{1}{1-\mathrm{e}^{-t}} - \frac{1}{t} \right) \mathrm{d} t $$

share|improve this answer
    
This is great start, thanks. Now, why is the $\gamma$ equal to that integral, if we start with the definition $$\gamma = \lim_{n \rightarrow \infty} \left( \sum_{j=1}^\infty \frac{1}{j} - \ln n \right)$$ –  Simon S Jan 20 '12 at 17:36

Ok, first note that $\displaystyle\gamma = \lim (\,\sum_1^n \frac{1}{k} - \log k) = \lim(\,\sum_1^n \frac{1}{k} - \log (k + 1))$.

For $x>1$, $\displaystyle\frac{1}{x-1} = \int_1^\infty \frac{\mathrm{d} t}{t^x} = \sum_{n = 1}^\infty \int_n^{n = 1} \frac{\mathrm{d} t}{t^x}$

In addition, $\displaystyle \log (n + 1) = \int_1^{n+1} \frac{\mathrm{d}t}{t} = \sum_{k = 1}^n \int_k^{k+1} \frac{\mathrm{d}t}{t}$

So $\displaystyle\lim_{x \to 1^+} \sum_1^\infty \left( \frac{1}{n^x} - \frac{1}{x^n}\right) = \lim_{x \to 1^+} \sum_1^\infty \left(\frac{1}{n^x} - \int_n^{n+1} \frac{\mathrm{d}t}{t^x}\right)$ on the one hand and

$\displaystyle \gamma = \lim \left( \sum \frac{1}{n} - \log n \right) = \sum \left( \frac{1}{n} - \int_n^{n+1} \frac{\mathrm{d}t}{t} \right)$ on the other hand.

The second is a termwise limit of the former, and so they are equal. An application of the Weierstrass M-test gives uniform convergence of $\displaystyle\lim_{x \to 1^+} \sum_1^\infty \left( \frac{1}{n^x} - \frac{1}{x^n}\right)$, so that we can rearrange the order and we get

$$\lim_{x \to 1^+} \left( \zeta(x) - \frac{1}{x-1} \right) = \gamma$$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.